2014 IEEE Biomedical Circuits and Systems Conference (BioCAS) Proceedings 2014
DOI: 10.1109/biocas.2014.6981795
|View full text |Cite
|
Sign up to set email alerts
|

Wearable low-latency sleep stage classifier

Abstract: A wearable microsystem for low-latency automatic sleep stage classification and REM sleep detection in rodents is presented. The detection algorithm is implemented digitally to achieve low latency and is optimized for low complexity and power consumption. The algorithm uses both EEG and EMG signals as inputs. Experimental results using off-line signals from nine mice show REM detection sensitivity and specificity of 81.69% and 93.83%, respectively, with a latency of 39µs. The system will be used in a non-disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Sleep status is often an influential factor related to a patient s health status and is important to monitor [5,7]. In general, sleep is a dynamic process that varies from day to day; hence, it is important to assess multiple nights of sleep for medical, research, and wellness reasons [7,8]. Recent research has revealed that motion detection can be used to monitor sleep status [9].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep status is often an influential factor related to a patient s health status and is important to monitor [5,7]. In general, sleep is a dynamic process that varies from day to day; hence, it is important to assess multiple nights of sleep for medical, research, and wellness reasons [7,8]. Recent research has revealed that motion detection can be used to monitor sleep status [9].…”
Section: Introductionmentioning
confidence: 99%
“…Electromyography (EMG), which is a tool to record and evaluate the electrical activity produced by our skeletal muscles, is a potentially useful technique for this application. EMG has been extensively used in polysomnography (PSG) studies to evaluate the quality of sleep [4,5] and can provide information about the level of stress by recording from facial expressions during sleep to detect certain patterns in specific movements such as clenching. In addition to sleep studies, personalized EMG sensors capable of real-time decision making can be used to take measurements during daily activities in order to warn the user when an alarm event occurs.…”
Section: Introductionmentioning
confidence: 99%